2003
DOI: 10.1152/ajpcell.00537.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A-induced hair growth in mice is associated with inhibition of calcineurin-dependent activation of NFAT in follicular keratinocytes

Abstract: One of the most common side effects of treatment with cyclosporin A (CsA) is hypertrichosis. This study shows that calcineurin activity is associated with hair keratinocyte differentiation in vivo, affecting nuclear factor of activated T cells (NFAT1) activity in these cells. Treatment of nude or C57BL/6 depilated normal mice with CsA inhibited the expression of keratinocyte terminal differentiation markers associated with catagen, along with the inhibition of calcineurin and NFAT1 nuclear translocation. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 46 publications
6
51
0
Order By: Relevance
“…A promoter construct covering the Sp1 binding sites of the p21 WAF1/CIP1 promoter was activated by high Ca 2ϩ in a calcineurin-dependent manner and NFAT1͞2 was coprecipitated with Sp1. Gafter-Gvili et al (35) showed that cyclosporin A enhanced hair growth in the mouse in vivo and inhibited p21 WAF1/CIP1 induction in cultured follicular keratinocytes. In the present study, we showed that upon exposure of NHK cells to high Ca 2ϩ , NFAT1 was dephosphorylated, translocated into nuclei, and bound to the Sp1-binding site of the genomic p21 WAF1/CIP1 promoter in association with Sp1, replacing KLF16 from it.…”
Section: Discussionmentioning
confidence: 99%
“…A promoter construct covering the Sp1 binding sites of the p21 WAF1/CIP1 promoter was activated by high Ca 2ϩ in a calcineurin-dependent manner and NFAT1͞2 was coprecipitated with Sp1. Gafter-Gvili et al (35) showed that cyclosporin A enhanced hair growth in the mouse in vivo and inhibited p21 WAF1/CIP1 induction in cultured follicular keratinocytes. In the present study, we showed that upon exposure of NHK cells to high Ca 2ϩ , NFAT1 was dephosphorylated, translocated into nuclei, and bound to the Sp1-binding site of the genomic p21 WAF1/CIP1 promoter in association with Sp1, replacing KLF16 from it.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we took advantage of the robust ability of CSA to stimulate hair growth in mice (Paus et al 1989;Gafter-Gvili et al 2003) and alter SC quiescence (Horsley et al 2008) even when follicular SCs are refractory to tissue-level activation signals (Plikus et al 2008). Mice treated with a 3-d course of CSA during the second telogen, a time when HFs are in an extended period of quiescence, lose nuclear Nfatc1 expression within the bulge SC compartment (Fig.…”
Section: Inhibition Of Nfatc1 With Csa Induces Unique Gene Expressionmentioning
confidence: 99%
“…Nfatc1 activity is directly regulated by the phosphatase calcineurin (CN), which dephosphorylates Nfatc1 to induce its nuclear translocation and transcriptional activity (Rao et al 1997;Horsley and Pavlath 2002). Inactivation of Nfatc1 through skin-specific genetic knockout or treatment with cyclosporine A (CSA), an inhibitor of CN (Mattila et al 1990), results in precocious activation of HF growth in mice (Paus et al 1989;Gafter-Gvili et al 2003;Horsley et al 2008). Nfatc1 inhibition induces hair growth through precocious bulge cell proliferation (Horsley et al 2008), and it is not clear whether Nfatc1 inhibition accelerates bulge cell migration to induce HF growth, as in the native hair cycle (Zhang et al 2009).…”
mentioning
confidence: 99%
“…Oliver et al 9 demonstrated that oral CsA restored hair growth in the Dundee Experimental Bald Rat Model of AA by reducing the mononuclear cell infiltrate around the hair follicles and renewing hair growth. GafterGvili et al 10 reported that CsA-induced hair growth in mice was associated with the inhibition of the calcineurin-dependent activation of NFAT in the follicular keratinocytes. They found that CsA delays the duration of the terminal differentiation of hair follicular keratinocytes and it retards catagen induction.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin regulates the nuclear factor of activated T cells (NFAT) and it also induces T cell activation by regulating the interleukin-2 (IL-2) gene expression and increasing the production of IL-2, which stimulates the secretion of interferon-γ (IFN-γ) 9,10 .…”
Section: Introductionmentioning
confidence: 99%